FYR Macedonia : Financial Sector Assessment - World Bank (Washington, DC, 2012)
This Financial Sector Assessment (FSA) provides a summary of the main findings and recommendations of the joint International Monetary Fund (IMF)-World Bank Financial Sector Assessment Program (FSAP) update team that visited Macedonia from March 26 to April 8, 2008. The principal objective of the FSAP update was to assist the authorities in evaluating development progress and future challenges and assessing the potential vulnerabilities of the financial system in Macedonia. In addition to the aide memoire summarizing the key findings, six technical notes (TN) were prepared, including an update of compliance with the Basel core principles for banking supervision and TNs on stress testing, the financial safety net, securities markets, the insurance sector, and the pension sector.